2016
DOI: 10.1108/aia-07-2016-0019
|View full text |Cite
|
Sign up to set email alerts
|

The clinical utility of social information processing theory in assessing and treating offenders with autism spectrum disorder

Abstract: Purpose: Social deficits are central within conceptualisations of autism spectrum disorder (ASD), and seperately linked to offending behaviour. Social problem solving interventions are often used with offenders, but little research has examined the social information processing (SIP) skills of individuals with ASD and a history of criminal offending behaviours.Design/methodology/approach: This conceptual paper will introduce the SIP model, review SIP research as applied to those with ASD and in forensic popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 120 publications
(162 reference statements)
0
4
0
Order By: Relevance
“…According to the SCIP, the first step of social-cognitive information-processing is the correct encoding and processing of others’ emotions to make moral judgments (Chester & Langdon, 2016 ; Lemerise & Arsenio, 2000 ). Previous studies identified positive relationships between emotion recognition and later SCIP steps (e.g., problem identification and solution, goal clarification, response selection) in TD children with and without mild intellectual impairments (Bauminger et al, 2005 ; Meyer et al, 2006 ; Schultz et al, 2004 ; van Nieuwenhuijzen & Vriens, 2012 ) and children with autism (Russo-Ponsaran et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the SCIP, the first step of social-cognitive information-processing is the correct encoding and processing of others’ emotions to make moral judgments (Chester & Langdon, 2016 ; Lemerise & Arsenio, 2000 ). Previous studies identified positive relationships between emotion recognition and later SCIP steps (e.g., problem identification and solution, goal clarification, response selection) in TD children with and without mild intellectual impairments (Bauminger et al, 2005 ; Meyer et al, 2006 ; Schultz et al, 2004 ; van Nieuwenhuijzen & Vriens, 2012 ) and children with autism (Russo-Ponsaran et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though there is quality research providing empirical support for individual risk factors and predictors of aggression in children with autism, it largely lacks integration, which hinders the effective understanding, prevention, and treatment of aggressive behavior (Chester & Langdon, 2016 ). The present work is based on the multifaceted Social Cognitive Information-Processing models (SCIP models; Crick & Dodge, 1994 , 1996 ; Huesmann, 1998 ; Lemerise & Arsenio, 2000 ) because they are to date the most influential and comprehensive frameworks, which are most widely applied to explain aggressive behavior (see reviews Fontaine, 2008 ; Larkin et al, 2013 ; Smeijers et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Social deficits are central within conceptualisations of autism spectrum disorder (ASD) and symptomology, and plausibly linked to offending behaviour (ASD). This suggests a need for research into social problem-solving interventions which take into account the social information processing skills of individuals with ASD as explored by Chester and Langdon in their paper, "The clinical utility of social information processing theory in assessing and treating offenders with autism spectrum disorder" (Chester and Langdon, 2016). Similarly, little is known about how the social and communication deficit impacts on rehabilitation work in forensic settings, particularly in the context of intellectual disability (Dobbinson, 2016).…”
Section: Direction Of Future Researchmentioning
confidence: 99%
“…While different types of NDD are difficult to distinguish at the neuropsychological level, more severe problems with Theory of Mind in individuals with ASD [39•] might make this group particularly vulnerable to HAI by making it difficult for them to envision that another person's intent may be non-hostile when the outcome is negative [20,40]. This might explain the link between Theory of Mind and social anxiety or aggression [41][42][43].…”
Section: Introductionmentioning
confidence: 99%